2005
DOI: 10.1111/j.1467-9310.2005.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Patent-based inventor profiles as a basis for human resource decisions in research and development

Abstract: Profiles of inventors' technological competence are a valuable source of information for decision‐making in research and development (R&D) management, e.g. concerning inventor assessment, human resource development and R&D team‐building. In the following exposition, a new method of inventor profiling will be put forward, which is based in particular on semantic patent analysis and multidimensional scaling. First, in the course of semantic patent analysis, specialized software, equipped with a natural language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 25 publications
0
54
0
4
Order By: Relevance
“…In addition, SNA techniques can derive information on corporate strategies by considering technological context information with the inventors, such as technological fields from patent classification, invention date, and assignee's business domain. Moehrle, Walter, Geritz, and Müller [16] suggested a method for supporting human resource decision making in R&D organization from the perspective of technological strategy. The research extracted researcher's technological profiles, technological knowledge, and their clusters by analyzing technological description in patents, and then they also analyzed technological context information, patent classification, and technological description of the classification, to complement the analysis results.…”
Section: Patent Co-inventor Network Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, SNA techniques can derive information on corporate strategies by considering technological context information with the inventors, such as technological fields from patent classification, invention date, and assignee's business domain. Moehrle, Walter, Geritz, and Müller [16] suggested a method for supporting human resource decision making in R&D organization from the perspective of technological strategy. The research extracted researcher's technological profiles, technological knowledge, and their clusters by analyzing technological description in patents, and then they also analyzed technological context information, patent classification, and technological description of the classification, to complement the analysis results.…”
Section: Patent Co-inventor Network Analysismentioning
confidence: 99%
“…R&D effort-strategic resource allocation to R&D projects to improve technological capabilities in specific technological domains-is directly aligned with strategic directions of a firm, because the goal of R&D is basically to obtain technological capabilities for sustaining competitive advantage and companies never spend money on-or allocate their resources to-any business or technology that deviates from their strategic direction. From the resource-based view, intangible resources, mostly human resources, are a major determinant of a firm's decision for internal R&D and R&D human resources generally occupy the most important portion of R&D expenditure [6,9,[14][15][16][17][18][19]. Therefore, R&D human resource allocation can be a proxy variable to represent a firm's R&D efforts on specific technological domains.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, an SAO structure contains and represents the key concept of a system. In addition, it can express the means-end relationship in a problem-solving format; the AO states the problem to be done, and the S forms the solution (Moehrle et al, 2005). For this reason, the SAO structures found in the specification and claims of patents have been considered to represent the know-how and expertise of the inventor of a patent and may even reflect the key concepts of the invention (Bergmann et al, 2008;Yoon et al, 2013).…”
Section: The Concept Of Functionmentioning
confidence: 99%
“…Moehrle et al (2005) suggested a method that profiles the technological capability of inventors for inventor assessment, human resource development, and R&D team-building. In the study, they extracted SAO structures from patents and mapped the patents onto a two-dimensional space by comparing similarities among patent SAO structures.…”
Section: Function-based Studies For Technology Intelligencementioning
confidence: 99%
See 1 more Smart Citation